Acute antidepressant drug administration and autobiographical memory recall: a functional magnetic resonance imaging study. - Papadatou-Pastou, M; Miskowiak, K; Williams, J; Harmer, C; Reinecke, A (2012)
Antidepressants affect memory and neural responses to emotionally valenced stimuli in healthy volunteers. However, it is unclear whether this extends to autobiographical memory for personally experienced events. The current study investigated the effects of acute administration of the antidepressant reboxetine on emotional autobiographical retrieval in healthy volunteers (14 men, 10 women). Functional magnetic resonance imaging was used in a double-blind between-groups investigation with reboxetine (4 mg) and placebo. Consistent with previous reports using lab-based stimuli, neural activation in the processing of positive versus negative memories was reduced following reboxetine compared with placebo in the left frontal lobe (extending into the insula) and the right superior temporal gyrus. This was paired with increased memory speed in volunteers given reboxetine versus placebo. The effect of reboxetine on emotional memory extends to recall of personally experienced events. Such effects may be relevant to the cognitive improvements found with recovery from depression and with the mechanism of action of contemporary antidepressant drugs.